استفتا اور فتوے کے باہمی تعلق کی معنویت: فتاویٰ مفتی محمود کے عائلی مسائل کا نموذجی مطالعہ ----------------------------------------------------- Meaningfulness of Istifta and Fatwa: An Exemplary Study of some Family Issues of Fatawa Mufti Mahmud - الرحمن, سعید (FIKR-O NAZAR فکر ونظر, 2016)
The fatwa is a legal opinion of a mufti. It is intended to elucidate the legal issue at the request of an inquirer. A mufti primarily concentrates on the question of the inquirer without indulging into its context and prevailing circumstances. It is called comprehension of hukm. But some times the mufti tends to investigate about the situation of inquirer which is called comprehension of situation. In this article some legal fatawa from Fatawa Mufti Mahmud are taken into consideration for evaluation the meaningfulness between fatwa and istifta.